Analyzing Students' Consumptive Behavior: The Impact of Parental Socio-Cultural and Economic Factors - Herman Philips Dolonseda; Johny Taroreh; I Kadek Satria Arsana (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This study examines the consumptive behavior of students in the coastal regency of the Sangihe Islands, focusing on the socio-cultural and economic influences of their parents. Using a survey method with a questionnaire, data were collected from 413 high school students across various schools. The findings reveal that parental socio-cultural and economic factors significantly impact students' consumptive behavior. Additionally, external influences such as social media, advertisements, public figures, product branding, and peer expectations also play a substantial role. These insights are intended to help parents and educators better understand and address the dynamics of consumptive behavior among adolescents.